The January 11, 2018, Mw 6.0 Bago-Yoma, Myanmar earthquake : a shallow thrust event within the deforming Bago-Yoma range - Fadil, Wardah (2021)
On January 11, 2018 (18:26 UTC), a Mw 6.0 earthquake occurred approximately 30 km west of the Sagaing Fault in the Bago-Yoma Range (BYR). Using a local broadband seismic network and regional seismic stations, we refine the locations and moment tensors of the earthquake sequence. We relocate 98 earthquake epicenters and determine the focal mechanism and centroid depth of the mainshock and 20 aftershocks with Mw > 4. The relocated epicenters cluster in a NW-SE direction that is consistent with the strike of the mainshock fault plane solution and the slip distribution derived from ALOS-2 interferometric synthetic aperture radar observations. Most of the aftershocks have a pure thrust focal mechanism similar to the mainshock, except for four strike-slip aftershocks. The refined locations and moment tensors of the thrust events clearly delineate a fault dipping ∼40° to the southwest at a depth range of 3–7 km, indicating that the earthquake sequence ruptured a previously unmapped, active fault. We interpret the earthquake sequence to be associated with pre-existing faults within the BYR anticlinorium. This earthquake sequence and historical seismicity indicate that the upper crust of the BYR is highly stressed, resulting in ongoing distributed deformation between the oblique Rakhine megathrust and the dextral Sagaing Fault. The seismic hazard posed by these active faults has been increasing with the development of infrastructure such as dams within the BYR. Our study highlights the need for high-resolution earthquake source parameter and strong ground motion attenuation studies for further understanding of the neotectonics of Myanmar and its related seismic hazard.